PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011) - Satria, Emerald Dany; Daljono, Daljono (Diponegoro Journal of Accounting, 2014)
Nowadays, the company in addition to oriented economic aspects are also required to have a social and environmental responsibility. Social and environmental responsibility is known as Corporate Social Responsibility (CSR). The era of globalization requires companies to engage in CSR practices because they were considered capable of supporting sustainable development for all humanity, while stakeholders requires companies to engage in CSR practices so that their interests are considered. Nevertheless, the implementation of CSR for the company itself generated much debate, especially when linked with the company's financial performance. This study aims to determine how the effect of the practice of Corporate Social Responsibility (CSR) by companies to the corporate financial performance, specifically company's short-term profitability (accounting-based view) and company’s future profitability (market-based view). The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) period in 2011 with the total sample were 112 companies which determined by purposive sampling method. The results of this study show that CSR has no significant effect on the company's short-term profitability but has positive and significant effect on the company’s future profitability.